"Best for everyone concerned" or "Only as a last resort"? Views of Australian doctors about sterilisation of men and women with intellectual disability. Issue Volume 39:Issue2(2014) (3rd April 2014) - Gilmore, Linda; Malcolm, Laura
Abstract: Background Doctors have the potential to influence opportunities for normative life experiences in the area of sexuality for individuals with intellectual disability (ID). Method In Study One, 106 doctors completed the Attitudes to Sexuality Questionnaire (Individuals with an Intellectual Disability). In Study Two, 97 doctors completed a modified form of the questionnaire that included additional questions designed to assess their views about sterilisation. Results Attitudes were less positive about parenting than about other aspects of sexuality, and less sexual freedom was seen as desirable for adults with ID. A surprising number of doctors agreed that sterilisation was a desirable practice. Study Two provided data about the conditions under which sterilisation was endorsed. Most doctors reported they had not been approached to perform sterilisations. Only 12% believed medical practitioners receive sufficient training in the area of disability and sexuality. Conclusions The findings have implications for training and professional development for doctors.